Therapeutic Plasticity of Neural Stem Cells - Ottoboni, Linda; von Wunster, Beatrice; Martino, Gianvito (Frontiers in Neurology, 2020)
Neural stem cells (NSCs) have gained significant scientific and commercial interest in the last 15 years. Given their plasticity, defined as the ability to develop into different phenotypes inside and outside of the nervous system, with capacity of almost unlimited self-renewal, of releasing trophic and immunomodulatory factors and of exploiting temporal and spatial dynamics, NSCs have been proposed for i) neurotoxicity testing; ii) cellular therapies to treat CNS diseases; iii) neural tissue engineering and repair; iv) drug target validation and testing; v) personalized medicine. Moreover, given the growing interest of developing cell-based therapies to target neurodegenerative diseases, recent progresses in developing NSCs from human-induced pluripotent stem cells have licensed an analog of endogenous NSCs Herein, we will review the current understanding on emerging conceptual and technological topics in the neural stem cell field such as deep characterization of the human compartment, single cell spatial-temporal dynamics, reprogramming from somatic cells or NSC manipulation and monitoring. Altogether those aspects contribute to further disentangle NSC plasticity to better exploit the potential of those cells that in the future might offer new strategies for brain therapies.